2008
DOI: 10.1136/adc.2007.120220
|View full text |Cite
|
Sign up to set email alerts
|

Fetal alcohol syndrome: a prospective national surveillance study

Abstract: Our data are the only prospective national data available on FAS throughout the world. These findings highlight the severity, complexity and impact of FAS, the need for effective strategies for prevention, and the necessity for education to facilitate earlier diagnosis, referral and reporting of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 19 publications
6
106
0
1
Order By: Relevance
“…In the USA, the estimated prevalence is 2e7 cases per 1000 live births [23]. Studies from Europe [24], Africa [25e27], Israel [28], Australia [29,30], and Russia [31] show a much higher prevalence. The highest prevalence to date has been reported from high-alcohol-consuming regions of South Africa (90 per 1000 births) [32].…”
Section: Fetal Alcohol Syndromementioning
confidence: 99%
“…In the USA, the estimated prevalence is 2e7 cases per 1000 live births [23]. Studies from Europe [24], Africa [25e27], Israel [28], Australia [29,30], and Russia [31] show a much higher prevalence. The highest prevalence to date has been reported from high-alcohol-consuming regions of South Africa (90 per 1000 births) [32].…”
Section: Fetal Alcohol Syndromementioning
confidence: 99%
“…5 The terminology Fetal Alcohol Spectrum Disorders (FASD) has been coined to define any defect caused by embryonic or prenatal alcohol exposure. 1,[6][7][8][9] Due to the high prevalence of drinking, FASD is a widespread disease in many ''Westernized'' nations. 8 In the United States alone, amounts of ethanol consumption during pregnancy vary greatly.…”
mentioning
confidence: 99%
“…In a high-risk community in South Africa, the prevalence in first graders was as high as 65.2 -74.2 per 1000 children . In Australia, the prevalence of FAS in children under the age of 5 between 2001 and 2004 was estimated to be 0.037 per 1000 non-Indigenous children, or 1.46 per 1000 Indigenous children (Elliott et al, 2008). The authors of this study did indicate that these figures are likely to be underestimated due to difficulties associated with diagnosis.…”
Section: Evidence In Humansmentioning
confidence: 62%
“…A study on 92 Australian cases of Fetal Alcohol Syndrome (discussed in more detail in Section 1.3.1) between 2001 and 2004 found that 78.3% of affected children had also been exposed to a secondary drug (e.g., nicotine, marijuana, and heroin) during gestation (Elliott et al, 2008). Of these, nicotine was the most frequently identified as being used with alcohol, with 67.4% of affected children also being identified as exposed to nicotine during pregnancy (Elliott et al, 2008), despite only 17.3% of mothers who were surveyed Australia-wide, who gave birth in 2003, admitting to smoking cigarettes during their pregnancies (Laws et al, 2006).…”
Section: Gestational Alcohol and Tobacco Usage In Australiamentioning
confidence: 99%
See 1 more Smart Citation